The Influence of Transformational Leadership on Teacher Performance Through Work Motivation and Organizational Commitment: A Systematic Literature Review - Firmansyah, Diyan; Dermawan, Oki; Kusuma Yusuf, Trisna (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
School leadership plays a crucial role in determining policy direction, organizational culture, and the quality of education in schools. In the context of educational organizations, transformational leadership is seen as capable of enhancing work motivation and strengthening teachers' organizational commitment, thereby improving their performance in carrying out their professional duties. This study aims to synthesize various research findings regarding the impact of transformational leadership on teacher performance through work motivation and organizational commitment. The review was conducted using the Systematic Literature Review (SLR) method with Barbara Kitchenham's model, which includes three stages: planning, conducting, and reporting. A total of 10 research articles were analyzed using a descriptive-thematic approach to identify patterns, relationships between variables, and the theoretical and practical contributions of previous studies. The synthesis results show that transformational leadership plays an important role in improving teacher performance both directly and through the enhancement of work motivation and organizational commitment. The effectiveness of transformational leadership is also influenced by a supportive work environment and organizational support in developing teachers' professionalism. Thus, school leaders need to apply transformational leadership styles that can foster teachers' motivation and commitment, creating a productive, professional, and quality-oriented work environment.